Population challenges and development goals - United Nations. Department of Economic and Social Affairs (New York, 2005)
This report presents a succinct overview of demographic trends worldwide, for major areas and selected countries. It covers population size and growth, urbanization and city growth, population ageing, fertility and contraception, mortality and international migration. In addition, it includes a section on population policies, in which the concerns and responses of Governments with respect to major trends are summarized. The report also considers the contribution of the implementation of the Programme of Action of the International Conference on Population and Development (ICPD), in all its aspects, to the achievement of the internationally agreed development goals, including those contained in the United Nations Millennium Declaration.
Keywords: Population